CONFLICT IN SCHOOL CLIMATE: A SYNOPSIS OF ITS NATURE, CAUSES, EFFECTS AND MANAGEMENT APPROACHES - Martins Fabunmi; Chinyere N. Alimba (African Journal of Educational Management, 2021)
School climate is a functional variable that determines the nature of social activities that will take place in a school. Its functionality is based on how emerging conflicts are constructively managed to make positive impacts on people and the system. Based on this, the study examined the nature, causes, effects and management approaches of conflict in the secondary school climate in Adamawa State. The study adopted a descriptive research design, using a questionnaire entitled “Conflict and School Climate Questionnaire (CSCQ)” to gather the required data. Seven hundred and sixty teachers (760) were selected through a random sampling technique from Yola and Numan educational zones in the state. Percentage, chart and graph were used to analyse the data collected. The result shows that teacher-student conflict (TSC) was the main form of conflict confronting teachers in secondary school climates. The study also discovered that collaborating conflict handling style was the major approach that teachers employ to resolve conflict, followed by accommodation approach. The causes and effects of conflict in secondary school climate were discovered. Implications for peaceable classroom and policy options were highlighted.